MEASUREMENT OF EXCLUSIVE BRANCHING FRACTIONS OF HADRONIC ONE-PRONG TAU-DECAYS - Acciarri, M; Adam, A; Adriani, O; Aguilarbenitez, M; Ahlen, S; Alcaraz, J; Aloisio, A; Alverson, G; Alviggi, M; Ambrosi, G; An, Q; Anderhub, H; et al. (1995)
We have measured the branching fractions for the hadronic τ decays, τ → π Knπ° ν (0≤ n ≤3), with the L3 detector at LEP. Multiphoton final states are analyzed using the fine-grained, high-resolution electromagnetic calorimeter. The decay channels are identified using a neural network method. The results are: BR(τ → π Kν) = (11.82 ± 0.26 ± 0.43) %, BR(τ → π Kπ° ν) = (25.05 ± 0.35 ± 0.50)%, BR(τ → π K2π° ν) = (8.88 ± 0.37 ± 0.42)%, BR(τ → π K3πδ ν) = (1.70 ± 0.24 ± 0.38)%, where the first error quoted is statistical, the second systematic. © 1995.